+0  
 
0
429
4
avatar
Solve for x

2(27)^x = 9^(x-1)

Please and thank you!
Guest Mar 28, 2012
 #1
avatar+3077 
0
2*(27^x) = 9^(x-1)
ln on both sides:
ln( 2*(27^x) ) = ln( 9^(x-1) )
x * ln( 27 ) + ln( 2 ) = (x-1) * ln( 9 )
x * ln( 27 ) + ln( 2 ) = x * ln( 9 ) - ln( 9 )
x * ln( 27 ) = x * ln( 9 ) - ln( 9 )-ln( 2 )
x * ln( 27 ) = x * ln( 9 ) - ln( 9 )-ln( 2 )
x * ln( 27 ) -x * ln( 9 ) = - ln( 9 )-ln( 2 )
x * ( ln( 27 ) - ln( 9 ) ) = - ln( 9 )-ln( 2 )
x = (- ln( 9 )-ln( 2 )) / ( ln( 27 ) - ln( 9 ) )
[input](- ln( 9 )-ln( 2 )) / ( ln( 27 ) - ln( 9 ) )[/input]
admin  Mar 28, 2012
 #2
avatar
0
2(27)^x = 9^(x-1)
Ich gehe davon aus, dass zwischen 2 und der Klammer ein Mal steht. Wenn das der Fall ist, so ist die Klammer unnötig, und ich lasse sie gleich weg.

Zuerst logarithmieren auf beiden Seiten, entweder mit ln oder log.
log (2*27^x)= log (9^(x-1))

Dann Anwenden der Rechenregeln für log

1) log (a*b) = log (a) + log(b)
log (2) + log (27^x)= log (9^(x-1))

2) log (a^b) = b*log (a)
log(2) + x*log (27) = (x-1)*log (9)

Nun die Klammer (auf der rechten Seite) durch Ausmultiplizieren auflösen:
log(2) + x*log (27) = x*log (9) -1*log (9)
also
log(2) + x*log (27) = x*log (9) - log (9)

alle Ausdrücke, die x enthalten durch + oder - auf eine Seite bringen, die anderen auf die andere Seite
log (2) + log (9) = x*log (9) - x*log (27)

auf der rechten Seite x herausheben
log (2) + log (9) = x*(log (9) - log (27))

durch (log (9) - log (27)) dividieren
x=(log (2) + log (9))/(log (9) - log (27))

beim Eingeben in den Taschenrechner, die Klammern um den Nenner bzw. um den Zähler nicht vergessen!

Good luck!
Ernie
Guest Mar 28, 2012
 #3
avatar
0
I didn't realize that you wrote in English ... sorry!

First use logarithm (ln or log) on both sides of the equation.
log (2*27^x)= log (9^(x-1))

use rules for logarithm

1) log (a*b) = log (a) + log(b)
log (2) + log (27^x)= log (9^(x-1))

2) log (a^b) = b*log (a)
log(2) + x*log (27) = (x-1)*log (9)

get rid of brackets by multiplying
log(2) + x*log (27) = x*log (9) -1*log (9)
or
log(2) + x*log (27) = x*log (9) - log (9)

all expressions that contain x are put on one side of the equation (by using + or -). the other expressions are put on the other side.
log (2) + log (9) = x*log (9) - x*log (27)

extract x on the right side
log (2) + log (9) = x*(log (9) - log (27))

divide by (log (9) - log (27))
x=(log (2) + log (9))/(log (9) - log (27))

don't forget to use brackets when you type it into the calculator!

Good luck!
Ernie
Guest Mar 28, 2012
 #4
avatar+3077 
0
admin:

Good luck!
Ernie



very nice work.
admin  Mar 28, 2012

32 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.